1998
DOI: 10.1590/s0066-782x1998001000004
|View full text |Cite
|
Sign up to set email alerts
|

Monitorização residencial da pressão arterial e monitorização ambulatorial da pressão arterial versus medida de pressão arterial no consultório

Abstract: Purpose -To compare both home blood pressure measurement (HBPM) and ambulatory blood pressure monitoring (ABPM) with office blood pressure measurement (OBP); and also to compare the correlation between HBPM and OBP with LVMI (left ventricular mass index).Methods (r= 0.39 / 0.49, p<0.05, systolic and diastolic, respectively) than OBP (r= 0.02/ 0.22, p>0.05, systolic and diastolic, respectively). Conclusion -This study showed that HBPM has a better correlation with LVMI than OBP. Key Monitorização Residencia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
1
6
1
5
Order By: Relevance
“…The frequency of anti-hypertensive drug use among hypertensive patients was similar in both genders (p=0.095). no correlation between LVMI and DAP was observed, which is in disagreement with a previous study that found a significant correlation of LVMI with SAP and DAP using HBPM 27 . This study did not assess the correlation with PP.…”
Section: Discussioncontrasting
confidence: 99%
“…The frequency of anti-hypertensive drug use among hypertensive patients was similar in both genders (p=0.095). no correlation between LVMI and DAP was observed, which is in disagreement with a previous study that found a significant correlation of LVMI with SAP and DAP using HBPM 27 . This study did not assess the correlation with PP.…”
Section: Discussioncontrasting
confidence: 99%
“…This method has been recommended 3 , since it helps in treatment adhesion and is superior to the casual measurements taken at the doctor's office in regard to target organ lesions 43,44 . In comparison to in-office measurements the in-home blood pressure measurements offer a greater number of readings, better reproducibility and data storage in the unit's memory chip.…”
Section: Sem Medicaçãomentioning
confidence: 99%
“…Essa não é uma técnica inovadora, pois já em 1940 40 havia sido demonstrado que a medida residencial, apresentava valores de 30 a 40mmHg mais baixos do que a medida no consultó-rio. Comparando-se os valores de medida da pressão no consultório com a monitorização ambulatorial da pressão arterial e a medida residencial verificou-se que a residencial apresentou valores mais baixos do que a monitorização ambulatorial da pressão arterial e a pressão de consultório 41 . Com o desenvolvimento de equipamentos compactos, confiáveis, validados e de preços mais acessíveis, o procedimento se tornou viável para uso em larga escala na prática clínica diária e na pesquisa.…”
Section: Importância Da Monitorização Residencial Da Pressão Arterialunclassified
“…Em nosso meio foi demonstrada melhor correlação da medida residencial com índice de massa de ventrículo esquerdo quando se compara com a medida de consultório 41 .…”
Section: Valor Clínico Da Monitorização Residencial Da Pressão Arterialunclassified